Implementation of multi-service ijarah financing in Islamic microfinance institutions: SWOT analysis - Istikharoh, Maya; Fitriyani, Yeny; Purwanto, Purwanto (LPPM ISNJ Bengkalis, 2025)
Purpose – This study aims to explore the implementation of multi-service ijarah financing in the Artha Bahana Syariah Tempuran through SWOT analysis. Method – This study uses a mixed approach that combines quantitative and qualitative. Data sources come from primary and secondary data in the form of observations, interviews, questionnaires, and literature. Respondents included 20 people and were complemented by four key informants. Data analysis techniques use the SWOT matrix, IFAS, and EFAS for a comprehensive understanding. Findings – The findings of this study identify that internal and external factors are crucial in shaping multi-service ijarah financing. Among the strengths identified are good and friendly service, public trust, strategic location, fast process, and easy procedures, which can significantly increase the promotion of multi-service ijarah financing. In addition, there are many opportunities in the predominantly Muslim community, strong member loyalty, and the growing needs of the community. However, challenges such as limited human resources, a primarily local marketing focus, and threats from competition and economic instability need to be addressed. Implications – This study can deepen the understanding of SWOT theory in multi-service ijarah financing and offer practical insights for developing more effective financing strategies.